Creative Strategy Live Streaming on TikTok Skintific.id Account in Increasing Engagement During the 2025 Period - Rachman, Nadia Maudina; Rasyid, Haryadi Arief Nuur (Jogjakarta Communication Conference (JCC), 2025)
TikTok, is one of the most famous social media platforms and has grown rapidly, especially for online marketing needs. TikTok has innovative and interactive features such as live streaming that allows brands to communicate directly with their audience to increase engagement and product marketing. @skintific.id has utilized live streaming to promote their skincare products, connect with customers, and provide incentives. With this feature, Skintific is able to record high engagement rates and build closer relationships with the audience. However, on the other hand @skintific.id must continue to compete with other companies such as Somethinc and The Ordinary, which also use different methods for live streaming. This research aims to analyze the live streaming creative strategy used by Skintific.id to increase user interaction and attract attention on TikTok. The method used in this research is a descriptive qualitative method. Data collection techniques using observation and interview techniques. The data validity test used in this research is the source triangulation technique to compare the data obtained from one informant with other informants. In addition, this study will also use method triangulation techniques to compare data obtained through interview techniques with data obtained through observation techniques. The data analysis technique uses the theory of miles, namely reducing data, presenting data, concluding data, and checking data validity. The results of the study show that to increase engagement, @skintific.id designs its live streaming schedule consistently so that it is easier for the audience to always watch it. The live streaming schedule is always updated through various social media platforms owned by Skintific.id. Regarding the content on live streaming @skintific.id always prioritizes the live streaming feature to promote their products, attract audience attention, and interact with users. In addition, in its live streaming sessions @skintific.id also always provides direct interaction, exclusive promotions, product demos, collaboration with influencers, consistent time, and differentiation in content. To display more interesting content and be able to increase engagement among its audience, @skintific.id regularly analyzes the live streaming activities carried out by its competitors, so that @skintific.id can display content that is superior in terms of visual composition and in terms of the host character.